PENAMBAHAN ALAS MESIN DAN PEMBERIAN PEREGANGAN DINAMIS DI BAGIAN PROSES PEMOTONGAN SINGKONG MENURUNKAN BEBAN KERJA, KELUHAN MUSKULOSKELETAL, DAN MENINGKATKAN PRODUKTIVITAS KERJA PADA INDUSTRI KERIPIK SINGKONG - Meiza Anniza; Ketut Tirtayasa; I Made Muliarta (Program Studi Magister Ergonomi Fisiologi Kerja Pascasarjana Universitas Udayana Denpasar Bekerjasama dengan Perhimpunan Ergonomi Indonesia (PEI), 2017)
Cassava cutting machine is a tool to cut the cassava into thin sheets with a thickness of 1 to 2 mm. High base of work cassava cutting machine is under worker’s elbow height. So during the work, the workers took the cassava to put into the machine by means of bending and putting cassava to cutting machine one by one until the cassava is cut off. Ergonomics intervention is making an additional pad on cassava cutting machine. The purpose of this research was to prove the effect of adding pad machines and the provision of dynamic stretching at the cutting process of cassava reduce the workload, musculoskeletal disorders, and increasing work productivity at cassava chips industry. Research was conducted by the same design subject (treatment by subjects design) with a sample of nine workers. Workload by measured the pulse of the workers. Musculoskeletal disorders measured by nordic body map questionnaire, and productivity is measured by a comparison between the results of cuts cassava production is divided workload multiplied working time. Data analyzed by t - paired with a significant level of p <0.005. The analysis showed after adding pad machine occurs a significant difference (p <0.05) between before and after treatment: (1) decreases in workload of workers from 102.41 beats per minute become 95.51 beats per minute, (2) decrease musculoskeletal disorders from the average score of 33.56 into 31.56, and (3) increase work productivity from 1.64 to 3.58. It was concluded that the addition of base support and the provision of dynamic stretching at the process of cutting cassava reduce the workload, musculoskeletal disorders, and increasing work productivity in cassava chips industry. It is suggested in the effort to reduce the workload, musculoskeletal disorders, as well as increasing work productivity in cassava cutting workers so it is suggested to addition of base support and do dynamic stretching movements.